การเมืองในกระบวนการยกฐานะขององค์การบริหารส่วนตำบลขึ้นเป็นเทศบาล : ศึกษาเฉพาะกรณีองค์การบริหารส่วนตำบลกระทุ่มล้ม อำเภอสามพราน จังหวัดนครปฐม - ธีรเดช สิริอำไพรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this research was to study the opinion of the tambon administrative organizations (TAO) administrators, TAO members, local leaders and people the effects of the upgrading of TAO to municipality and study matters of fact in the sense of conflict problem between local elites group and local leaders group the effects of the upgrading to municipality. The hypothesis of this research is chairman, vice-chairman, deputy, TAO members and people will think to go to in the sense same of is support but kamnan and village headman’s official has will an opinion objects that different opinion of each be from the conflict in political structure, power and interests in the area. The data has been collected by depth interview and focus group by separate 4 groups of key informants : TAO administrators group, TAO members group, local leaders group and people group. The results of this study affirms some aspects of hypothesis that is to say TAO administrators group, TAO members group, local leaders group and people group think same at want to have upgrading to municipality. The results were local leaders group majority agree with upgrading goes up to municipality. The cause is from upgrading goes up can t is the municipality makes local leaders group loses power and interests because of there is the change transfers the power from local leaders to a politician in new organization is municipality. The position of member of the municipality assembly or management team faction in the municipality has high position more of TAO. Then make local leaders group no come out to act up resist or object upgrading. Thus about story conflict problem between local elites group and local leaders group then don t happen be make upgrading goes up to the municipality has no problem or obstacle.